Causitivity in English and Arabic: A Linguistic Syntactic Study (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The principal goal of this paper is to investigate and contrast the linguistic syntactic phenomenon of causitivity in English and Arabic. It also shows the differences and similarities regarding causitivity in the two languages. This paper comprises nineteen sections. They are as following:  an introduction ,objectives of the study, questions of the study, significance of the study, limitation of the study , data collection , methodology, causitivity ,English causitivity , the lexical process, the prefixation process , the suffixation process, the causative verbs in Arabic, the Arabic basic causitives, the Arabic derived causitives, the form ?famala , the form ? ist famala , analysis, conclusion, references and an appendix
Keywords: Arguments; Causative verbs; Nominative and Accusative Cases; Prefixation; Suffixation